Femmes et Environnement. Enjeux d'égalité pour toutes les femmes - Boivin, Martine (Le Réseau des Tables régionales de groupes de femmes du Québec, 2020)
Le Réseau des Tables régionales de groupes de femmes du Québec est un regroupement provincial composé des 17 Tables régionales de groupes de femmes au Québec. Il s’agit d’un regroupement féministe de défense collective des droits, qui travaille sur les questions mettant en jeu les intérêts et les droits des femmes. La spécificité du regroupement est représentée par l’expertise régionale développée par les Tables régionales dans les dossiers de la condition féminine. Porte-voix des régions auprès des instances nationales, le RTRGFQ favorise la prise de parole collective des Tables régionales, tout en respectant leurs particularités. Le RTRGFQ et les Tables régionales sont en action depuis plus de 20 ans pour favoriser la participation des femmes à la vie démocratique québécoise
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; charge mentale; charge émotionnelle; environnement; intersectionnalité; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; santé; thématiques

The work-life experiences of an invisible workforce: The case of live-in women migrant domestic workers in Malaysia - Wee Chan Au; Uracha Chatrakul Na Ayudhya; Tan, Yan Soon; Ahmed, Pervaiz K (Equality, Diversity and Inclusion: An International Journal, 2020)
Purpose>The purpose of this paper is to explore the work-life (WL) experiences of live-in women migrant domestic workers (MDWs), who represent a significant proportion of migrant workers globally. MDWs play a key role in enabling the work-life balance (WLB) of others, namely the middle-class households that employ them. Yet, their experiences have largely been invisible in mainstream WL literature. The authors draw on an intersectional approach to frame the WL experiences of this marginalized group of women at the intersection of being secondary labour segment workers, with significant legal and employment restrictions as migrant workers, who work and live in the same place as their employers.Design/methodology/approach>Qualitative interviews were conducted with 13 women MDWs from Indonesia and the Philippines working in Malaysia. The women talked about the meaning of work as MDWs, how they maintain familial connections whilst working abroad, and how they negotiate their WLB as live-in workers. Thematic analysis of the interviews focused on the intersection of the women’s multiple dimensions of disadvantage, including gender, class and temporary migrant-foreigner status, in shaping their accounts of the WL interface.Findings>Three thematic narratives highlight that any semblance of WLB in the MDWs’ lived experience has given way to the needs of their employers and to the imperative to earn an income for their families back home. The themes are: working as MDWs enables the women and their families back home to have a life; the co-existence of WL boundary segmentation and integration in relation to “real” and “temporary” families; and the notion of WLB being centred around the women’s ability to fulfil their multiple duties as MDWs and absent mothers/sisters/daughters.Research limitations/implications>The study is based on a small sample of live-in women MDWs in Malaysia, intended to promote typically excluded voices and not to provide generalizable findings. Accessing potential participants was a considerable challenge, given the vulnerable positions of women MDWs and the invisible nature of their work.Practical implications>Future research should adopt a multi-stakeholder approach to studying the WL experiences of women MDWs. In particular, links with non-governmental organizations who work directly with women MDWs should be established as a way of improving future participant access.Social implications>The study underscores the existence of policies and regulations that tolerate and uphold social inequalities that benefit primary labour segment workers to the detriment of secondary labour segment workers, including women MDWs.Originality/value>Extant WL literature is dominated by the experiences of “the ideal work-life balancers”, who tend to be white middle-class women, engaged in professional work. This study offers original contribution by giving voice to a taken-for-granted group of women migrant workers who make other people’s WLB possible. Moreover, the study challenges WL research by underscoring the power inequities that shape the participants’ marginal and disadvantaged lived experience of work, life, family and WLB.
Number: 5 Place: Birmingham Publisher: Emerald Group Publishing Limited
Keywords: 2000 à aujourd'hui; approches et analyses; asie; femmes migrantes*; femmes médecins; intersectionnalité; malaisie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travailleuses de la santé

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis